Whose community? which interpretation? : philosophical hermeneutics for the church - Westphal, Merold (Grand Rapids, Mich. : Baker Academic, 2009)
Merold Westphal introduces current philosophical thinking related to interpreting the Bible. Recognizing that no theology is completely free of philosophical "contamination," he engages and mines contemporary hermeneutical theory in service of the church. After providing a historical overview of contemporary theories of interpretation, Westphal addresses postmodern hermeneutical theory, arguing that the relativity embraced there is not the same as the relativism in which "anything goes." Rather, Westphal encourages us to embrace the proliferation of interpretations based on different perspectives as a way to get at the richness of the biblical text. --From publisher's description.
Hermeneutics 101: no interpretation needed? -- Hermeneutics 102 : a little historical background -- Against romantic hermeneutics : away from psychologism -- Objectivism and authorial privilege -- Revoking authorial privilege -- Rehabilitating tradition -- On not clinging to the prejudice against prejudice -- Art as the site of truth beyond method -- Performance, application, conversation -- Conversation and the liberal-communitarian debate -- The church as conversation -- Transcendence, revelation, and community.
Includes bibliographical references and index.
Keywords: Bible -- Hermeneutics; Hermeneutics -- Religious aspects -- Christianity; Gadamer, Hans-Georg, -- 1900-2002.